(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
The objective of this work is to analyze the site-specific scenography as na instrumento of transformation and construction of new meanings, experiences and occupation of public spaces from three meanings works: The plays “Bom Retiro 958 metros”, directed by Joca Reiners Terron and “Das saborosas aventuras de Dom Quixote de la Mancha e seu escudeiro Sancho Pança - um capítulo que poderia ter sido”, by André Carreira and the minisséries “A Pedra do Reino” by Ariano Suassuna, directed by Luiz Fernando Carvalho.